Rotational atherectomy with the new RotaPro system over RG3 guidewire in subadventitial retrograde highly calcified CTO PCI. Issue 2 (12th August 2019) - Iannaccone, Mario; Colangelo, Salvatore; Colombo, Francesco; Garbo, Roberto
Abstract: The following article describes the case report of a 52‐year‐old man who is affected by a right coronary artery occlusion treated with rotational atherectomy over retrograde guidewire RG3 in subadventitial space.